(How) Perceived Descriptive Underrepresentation Decreases Political Support: The Case of East Germans. Issue 1 (2nd January 2023) - Vogel, Lars
Abstract : This article asks whether the persistent descriptive underrepresentation of East Germans in Germany's elite positions contributes to lower levels of political support in Eastern Germany. Based on a population survey including a survey experiment, it shows that citizens in both parts of Germany perceive a descriptive underrepresentation of East Germans. This perception remains stable, even when new information is provided. It is, however, not an attitudinal prejudice about decoupled elites but also based on citizens' cognitions. Citizens assess this underrepresentation negatively drawing on its negative impact on legitimacy, efficiency, and substantive and symbolic representation. The interaction of perception and negative assessment decreases political support for community, regime and institutions. The perceived impairment of legitimacy and symbolic representation fuels the withdrawal of support more strongly than impaired efficiency and substantive representation. Since both East and West Germans' political support is connected to descriptive representation, self-interest and sociotropic considerations are relevant. The contribution confirms that the descriptive underrepresentation of East Germans is one determinant of the lower levels of political support for democracy in Eastern Germany impairing the efficiency and legitimacy of democracy in the entire country.